Nab-paclitaxel combined with cadonilimab (AK104) as second-line treatment for advanced gastric cancer: protocol for a phase II prospective, multicenter, single-arm clinical trial - Wei, Jing; Zhang, Pengfei; Hu, Qiancheng; Cheng, Xiaolong; Shen, Chaoyong; Chen, Zhixin; Zhuang, Wen; Yin, Yuan; Zhang, Bo; Gou, Hongfeng; Yang, Kun; Bi, Feng; et al. (Frontiers in Immunology, 2025)
BackgroundGastric cancer (GC) is one of the most prevalent malignant tumors worldwide, often diagnosed at an advanced stage with a poor prognosis. Paclitaxel, nab-paclitaxel, and irinotecan, either as monotherapies or in combination with ramucirumab, are currently standard second-line treatments for GC. However, the efficacy of these therapies is limited, necessitating the development of new combination strategies to improve response rates. Immune checkpoint inhibitors (ICIs) have shown success in first-line treatment for advanced GC, leading to interest in immune rechallenge strategies for second-line treatment. Re-challenging patients with ICIs after progression on first-line treatment may restore immune responses and provide additional clinical benefit. Recently, cadonilimab (AK104), a bispecific antibody targeting PD-1 and CTLA-4, has demonstrated promising antitumor activity when combined with chemotherapy in advanced gastric and gastroesophageal junction (GEJ) adenocarcinoma. However, the efficacy and safety of nab-paclitaxel combined with AK104 for the treatment of advanced GC remain unclear. Furthermore, identifying predictive biomarkers of efficacy is essential to developing personalized treatment strategies. This study aims to explore the safety and efficacy of nab-paclitaxel combined with AK104 as a second-line treatment for patients who have progressed after first-line chemoimmunotherapy, focusing on evaluating the therapeutic effect of ICIs rechallenge in gastric cancer.MethodsThis is a prospective, multicenter, open-label, single-arm Phase II clinical study. Eligible patients were histologically or cytologically diagnosed with unresectable recurrent or metastatic GC, failed first-line chemotherapy in combination with immune checkpoint inhibitor, aged between 18-75 years old, expected survival ≥3 months, and with a physical status of 0 or 1 in the Eastern Cooperative Cancer Group (ECOG). Enrolled patients will receive intravenous cadonilimab (AK104) 6 mg/kg on days 1, and 15, and intravenous nab-paclitaxel 100 mg/m2 every four weeks on days 1, 8, and 15. The primary endpoints were objective response rate (ORR), and secondary endpoints were disease control rate (DCR), progression-free survival (PFS), and overall survival (OS). The exploratory objective was to identify biomarkers associated with efficacy, mechanism of action, and safety. A total of 59 participants were planned to be recruited using Simon’s two-stage design. The trial was initiated in June 2024 in China.DiscussionThis study is the first prospective trial to evaluate the combination of nab-paclitaxel and cadonilimab as second-line treatment after first-line chemoimmunotherapy failure. By investigating immune rechallenge, it aims to reactivate anti-tumor immune responses and improve clinical outcomes in GC patients. The exploration of predictive biomarkers, such as ctDNA, TMB, MSI, PD-L1 expression, TIL profiles, and gut microbiota, will help personalize treatment and identify patients most likely to benefit from immune rechallenge. This trial could provide valuable insights into overcoming immune resistance and contribute to developing a promising second-line therapeutic strategy for advanced GC.Clinical trial registrationClinicalTrials.Gov, identifier NCT06349967